2018
DOI: 10.4178/epih.e2018011
|View full text |Cite
|
Sign up to set email alerts
|

Factors related to cancer screening behaviors

Abstract: OBJECTIVESThis study aimed to investigate the factors related to cancer screening behaviors (CSB).METHODSThe 2014 Korean Community Health Survey used for analysis. The dependent variable was CSB, and the independent variables were demographic, health behavioral, and regional factor. Propensity score matching (PSM) used to control health behavior and regional factors, which were influencing CSB. For statistical analysis, chi-square test and logistic regression analysis used.RESULTSLogistic regression analysis a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
14
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 21 publications
4
14
1
Order By: Relevance
“…Economic index showed a conflicting influence on compliance with cancer screening among previous existing studies (16,20,21,25,26). In our study, we observed that participants with lower income were more likely to uptake endoscopy screening, which was consistent with the results targeting rural population (20,25), but was inconsistent with results from many previous studies that explored determinants of screening PRs on cancers of stomach, liver, colorectal, breast, and cervix, where higher incomes were associated with higher PRs (21,26). One possible explanation is that the involved people with lower income had greater disadvantages in health service utilization in rural China (27), therefore they would prefer to participate in screening without financial cost.…”
Section: Discussioncontrasting
confidence: 56%
“…Economic index showed a conflicting influence on compliance with cancer screening among previous existing studies (16,20,21,25,26). In our study, we observed that participants with lower income were more likely to uptake endoscopy screening, which was consistent with the results targeting rural population (20,25), but was inconsistent with results from many previous studies that explored determinants of screening PRs on cancers of stomach, liver, colorectal, breast, and cervix, where higher incomes were associated with higher PRs (21,26). One possible explanation is that the involved people with lower income had greater disadvantages in health service utilization in rural China (27), therefore they would prefer to participate in screening without financial cost.…”
Section: Discussioncontrasting
confidence: 56%
“…Cancer onset inflicts physical and mental pain on patients and their families and puts them under financial strain. Furthermore, from the view of society, it leads to economic losses due to decreased human resources and productivity, while increasing national healthcare expenditures [4]. Hence, it is important to map out strategies for cancer prevention in order to reduce financial burden and suffering on individuals and for the nation as a whole.…”
Section: Introductionmentioning
confidence: 99%
“…Residence: Two studies [14,15] found that urban dwellers were more likely to adopt healthy habits and receive preventive health care than their rural counterparts. However, we found two articles with the contrast finding [16,17].…”
Section: Summary Of the Literature Reviewmentioning
confidence: 54%
“…Gender: Eight studies [14,16,[18][19][20][21][22][23] reported that female older adults were more likely to perform health promotion self-care (e.g., being compliant with hospital discharge instructions) than their male counterparts. However, five studies [15,[24][25][26][27] concluded that male older adults were more likely to adopt healthy habits.…”
Section: Summary Of the Literature Reviewmentioning
confidence: 99%